Fexofenadine with either montelukast or a low-dose inhaled corticosteroid (fluticasone) in the treatment of patients with persistent allergic rhinitis and newly diagnosed asthma - Ciebiada, Maciej; Gorska-Ciebiada, Malgorzata; Gorski, Pawel (Archives of Medical Science, 2009)
Introduction: Asthma often coexists in patients with persistent allergic rhinitis. The aim of this study was to investigate the effects of treatment with a combination of antihistamine (fexofenadine) and either an antileukotriene agent (montelukast) or a low-dose inhaled corticosteroid (fluticasone) in patients with persistent allergic rhinitis and newly diagnosed asthma. Material and methods: 40 patients with persistent allergic rhinitis and newly diagnosed asthma received fexofenadine (120 mg/day) with fluticasone (200 µg/day) for 6 weeks then fexofenadine (120 mg/day) with montelukast (10 mg/day) for another 6 weeks. Symptom scores, anterior rhinoscopy, spirometry and serum concentrations of soluble intercellular adhesion molecule 1 were evaluated before and after 6-week treatment periods. Results: The sICAM-1 serum concentration before treatment was 243.4 ±20.7 ng/ml, after treatment 221 ±20.4 ng/ml in the fexofenadine-fluticasone group; and before treatment was 240.9 ±19.8 ng/ml, after treatment 218.3 ±17.6 ng/ml in the fexofenadine-montelukast group. The total symptom score before treatment was 8.15 ±1.37, after treatment 3.625 ±0.77 in the fexofenadine-fluticasone group; and before treatment was 8.275 ±1.38, after treatment 3.55 ±0.78 in the fexofenadine-montelukast group. The asthma symptom score before treatment was 7.1 ±0.8, after treatment 2.1 ±1.5 in the fexofenadine-fluticasone group; and before treatment was 6.9 ±2.3, after treatment 1.7 ±1.4 in the fexofenadine-montelukast group. Conclusions: The combination of fexofenadine with either montelukast or a low-dose inhaled corticosteroid (fluticasone) equally reduces the serum sICAM-1 concentration and gives the same clinical effect in patients with persistent allergic rhinitis and newly diagnosed asthma.